Chronic Kidney Disease is Associated With Upper Tract Urothelial Carcinoma: A Nationwide Population-Based Cohort Study in Taiwan. Issue 14 (April 2016) - Chen, Jeng-Sheng; Lu, Chin-Li; Huang, Li-Chung; Shen, Cheng-Huang; Chen, Solomon Chih-Cheng
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Increased urinary tract malignancy has been reported in end-stage renal disease (ESRD). However, little is known about chronic kidney disease (CKD). This study is designed to explore the association between CKD and upper tract urothelial carcinoma (UTUC). Using Taiwan's Longitudinal Health Insurance Database, we studied CKD patients between January 2000 and December 2011. The non-CKD controls were selected at a ratio of 4:1 and frequency matched by gender, age group, and index date. We used the chi-square test and t test to analyze the sociodemographic information and comorbidities. Cox regression analysis was used to calculate the hazard ratio (HR) and 95% confidence interval (CI). The selected cases included 45, 321 CKD cases and 181, 284 controls. A significantly higher incidence of UTUC was noted in the CKD group (0.22% vs 0.07%, P  < 0.001). In univariate analysis, CKD, female gender, age, hypertension, hematuria, repeated urinary tract infection, bladder cancer, and ESRD were all associated with UTUC. In multivariate analysis, only CKD, female gender, age, hematuria, bladder cancer, and ESRD were significantly associated. The HR for CKD was 1.63 (95% CI: 1.26–2.13). Females had a higher HR of 1.38 (95% CI: 1.11–1.71). After excluding those patients who progressed to dialysis or kidney transplantation, the risk for CKD was still high, with an HR of 1.72 (95% CI: 1.33–2.33). CKD is a significant factor associated with UTUC. We should pay attention to the possibility of UTUC for CKD patients before they progress to ESRD.